2013
DOI: 10.1080/09593330.2012.679700
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pH on nitrite accumulation during wastewater denitrification

Abstract: The characteristics of nitrite accumulation during denitrification in mixed liquors with different pH values were studied. The mixed liquors were prepared by adding acclimated denitrifying activated sludge to synthetic wastewater with methanol (CH3OH) as the carbon source (chemical oxygen demand = 600 mg/L) and sodium nitrate (NaNO3) as the nitrogen source (NO3(-)-N = 50 mg/L). The results showed that the pH during denitrification could be kept constant using buffer solutions composed of KH2PO4, Na2HPO4 x 12H2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Nitrite accumulation in a batch test has already been reported in previous works performed at alkaline pH (Glass and Silverstein, 1998), (i) using a pure culture of Halomonas desiderata (Alquier et al, 2014) or (ii) using the same mi crobial consortium enriched with sediments polluted by lime works (Rizoulis et al, 2012;Bassil et al, 2015). The reduction rates of nitrite and nitrate were greatly impacted by the pH, the nitrite reduction being impacted on more strongly than the nitrate (Thomsen et al, 1994;Cao et al, 2013). One possible explanation could be the difference in the locations of bacterial enzymes.…”
Section: Microcosm Activity In Closed Bioreactorsmentioning
confidence: 64%
“…Nitrite accumulation in a batch test has already been reported in previous works performed at alkaline pH (Glass and Silverstein, 1998), (i) using a pure culture of Halomonas desiderata (Alquier et al, 2014) or (ii) using the same mi crobial consortium enriched with sediments polluted by lime works (Rizoulis et al, 2012;Bassil et al, 2015). The reduction rates of nitrite and nitrate were greatly impacted by the pH, the nitrite reduction being impacted on more strongly than the nitrate (Thomsen et al, 1994;Cao et al, 2013). One possible explanation could be the difference in the locations of bacterial enzymes.…”
Section: Microcosm Activity In Closed Bioreactorsmentioning
confidence: 64%
“…Schuch et al (2000) observed that a higher alkaline pH (>7.8) resulted in a lower denitrification rate and in an increasing nitrite concentration in the effluent. On the other hand, Cao et al (2013) concluded that nitrite accumulation was more serious at low pH than at high pH, regardless whether the pH of the mixed liquor was stabilized during denitrification. The major importance of the pH at such, it usually influences other parameters playing even a greater role in nitrite accumulation; among others, the balance of ammonium and ammonia in water is dependent on the pH, and the effect of free ammonia seems to be more pronounced.…”
Section: Tablementioning
confidence: 95%
“…Moreover, the pH variability from 10 to 9.2 could promote the permanent accumulation of nitrite in a concentration range of 2.3 ± 0.7 mM. Many factors, and especially the pH, may influence the nitrite and nitrate reduction rates and the effects of pH on the reduction rates of nitrite and nitrate can be different [7,37]. Denitrifying enzymes are relatively sensitive to pH values and there is a specific pH for each enzyme [38].…”
Section: Nitrite Accumulationmentioning
confidence: 99%